An Evaluation of Construction Processes of the Buildings Which Existed in Sayyid Mehmet Aga's Foundations in the 19th Century and Current Situations - Eyyamoglu, Mustafa; Pilehvarian, Nuran Kara (KARABUK UNIV, 2019)
In this study, reconstruction activities in Cyprus were investigated according to the information given in the El-Hac Es-Sayyid Mehmet Aga Foundation (1826). El-Hac Es-Seyyid Mehmet Aga was a former guardian in Ottoman Palace (Istanbul) who was appointed as a tax officer Cyprus in the early 19th century. Seyyid Mehmet Aga, during his stay in Cyprus constructed Mosque, Tekke, Mescit, and schools and he has foundations related to these structures. These foundations are available in the TRNC Vakiflar Administration, TRNC Girne National Archives and Research Department, Republic of Turkey Directorate General of Foundations Achieves. Most of the Islamic buildings registered in the Seyyid Mehmet Aga foundation are made up of the pre-existing, inadequate and ruined structures re-constructed and brought to the use of the Muslim Turkish Cypriot people. Nicosia Dukkanlaronu Mosque, Fethiye Mosque, Tahtakale Mosque, Lapta Mosque and Famagusta Kutup Osman Efendi Tomb are the architectural venues where the Turkish Cypriot Islamic culture has been performed and it is understood from archival documents that they are supported by various mites and foundations. Within the scope of the study, prior and restructuring processes of these structures were determined and findings were made about the current situation. These structures are the living documents of the Ottoman Period in Cyprus over 300 years, which describe the structuring of the Islam and Ottoman identity in island. These structures are important documents of the Turkish Cypriot Islamic Heritage. Due to political changing over time they lost their incomes and original shapes.
Keywords: Cyprus; Ottoman; Cultural heritage; Seyyit Mehmet Aga Vaqf; Mosque; Arts & Humanities - Other Topics